Summary of the application value of ultrasound imaging features in the clinical differential diagnosis of intramuscular capillary-type hemangioma and fibro-adipose vascular anomaly - Hu, Wen-Jia; Li, Hai-Ting; Fan, Zhi-Na; Gong, Yu-Bin; Guo, Xiao-Nan; Dong, Chang-Xian; Fan, Pan-Hong; Yang, Xiao; Wu, Gang (Frontiers in Oncology, 2023)
Objective To investigate the value of ultrasonography as a diagnostic aid in differentiating intramuscular capillary-type haemangioma (ICTH) from fibro-adipose vascular anomaly (FAVA). Methods A retrospective analysis was conducted of the clinical and ultrasound imaging data of 20 patients with ICTH and 45 patients with FAVA who were admitted to and pathologically confirmed in hospital between January 2013 and April 2023. The clinical and ultrasonographic appearances of the lesions in the two groups were compared and analysed. A stepwise regression analysis was performed, and a joint diagnostic equation was constructed using the final variables selected. The receiver operating characteristic (ROC) curve and indicators, including sensitivity and specificity, were used to evaluate the efficacy of the joint diagnostic model. Results The two groups of patients suffering from ICTH and FAVA presented a statistically significant difference (P < 0.05) in terms of ‘age’, ‘lesion size’, ‘fascial tail sign’, ‘presence of a fatty-tissue-like hyperecho around the lesion’, ‘blood flow’ and ‘presence of straight blood capillaries within the lesion’. Finally, the variables ‘fascial tail sign’ and ‘presence of straight blood capillaries within the lesion’ were selected to construct the model. The constructed joint diagnostic model had a sensitivity value of 70.0% (95% CI: 59.00–81.00), a specificity value of 98.0% (95% CI: 94.70–100.00) and a ROC curve value of 0.908, indicating the high efficacy of the combined diagnosis method. Conclusions Ultrasonography can be utilised to differentiate ICTH from FAVA, and the combined diagnosis method can further improve the technique’s diagnostic efficacy.